Association of Trismus With Quality of Life and Swallowing in Survivors of Head and Neck Cancer. (April 2022) - Jia, Zeyao; Li, Jinhong; Harrison, Christine; Pawlowicz, Elizabeth; Clump, David Anthony; Wasserman-Wincko, Tamara; Moore, Kelly; Johnson, Jonas T.; Nilsen, Marci Lee
Objective: We aim to (1) determine the prevalence and predictors of trismus and (2) examine the relationship of trismus, swallowing dysfunction, and quality of life (QOL) in survivors of head and neck cancer (HNC). Study Design: Case series with chart review. Setting: Multidisciplinary HNC survivorship clinic. Methods: Data on trismus and patient-reported outcomes were obtained from survivors of HNC between December 2016 and October 2019. Trismus was defined as a maximum interincisal opening ≤35 mm. QOL and swallowing dysfunction were measured with the University of Washington Quality of Life questionnaire and EAT-10 (Eating Assessment Tool–10), respectively. Linear regressions were applied to investigate the relationship of trismus with QOL and swallowing dysfunction. Results: Of the 237 survivors, 22.78% (n = 54) had trismus. Advanced stage of cancer (stage III/IV vs Tis-II, P = .002) and treatment (nonsurgical and surgery + adjuvant treatment vs surgery only, P = .006) were correlated with a higher prevalence of trismus. After controlling for cancer stage and treatment type, EAT-10 scores for survivors with trismus were 9.342 (95% CI, 6.262-12.423; P < .0001) higher than those without trismus. The University of Washington Quality of Life Physical and Social-Emotional subscales for patients with trismus were 14.088 (95% CI, 9.042-19.134; P < .0001) and 10.470 (95% CI, 4.793-16.147; P = .0003) lower than those without trismus, respectively. Conclusion: Trismus is a common, treatment-related consequence and is associated with increased symptoms of dysphagia and decreased QOL. Early detection and management of trismus in survivors of HNC are essential to optimize QOL and reduce morbidity.